XRN1 is a Species-Specific Virus Restriction Factor in Yeasts - Rowley, Paul A; Ho, Brandon; Bushong, Sarah; Johnson, Arlen; Sawyer, Sara L (bioRxiv, 2016)
In eukaryotes, the degradation of cellular mRNAs is accomplished by Xrn1p and the cytoplasmic exosome. Because viral RNAs often lack canonical caps or poly-A tails, they can also be vulnerable to degradation by these host exonucleases. Yeast lack sophisticated mechanisms of innate and adaptive immunity, but do use RNA degradation as an antiviral defense mechanism. One model is that yeast viruses are subject to degradation simply as a result of the intrinsic exonuclease activity of proteins involved in RNA metabolism. Contrary to this model, we find a highly refined, species-specific relationship between Xrn1p and the double-stranded L-A totivirus of different Saccharomyces yeast species. We show that the gene XRN1 has evolved rapidly under positive natural selection in Saccharomyces yeast, resulting in Xrn1p protein sequence divergence from one yeast species to the next. We also show that these sequence differences translate to differential interactions with yeast viruses, where Xrn1p from S. cerevisiae is most efficient at controlling the L-A virus that chronically infects S. cerevisiae, and Xrn1p from S. kudriavzevii being most efficient at controlling the L-A-like virus that we have discovered within S. kudriavzevii. All Xrn1p orthologs are equivalent in their interaction with another virus-like parasite, the Ty1 retrotransposon. Thus, the activity of Xrn1p against totiviruses is not an incidental consequence of the enzymatic activity of Xrn1p, but rather Xrn1p co-evolves with totiviruses to maintain its potent antiviral activity and limit viral propagation in Saccharomyces yeasts. Consistent with this, we demonstrated that Xrn1p physically interacts with the Gag protein encoded by the L-A virus, suggesting a host-virus interaction that is more involved that Xrn1p-mediated nucleolytic digestion of viral RNAs.